URGENSI LANDASAN PSIKOLOGI DALAM PELAKSANAAN BIMBINGAN DAN KONSELING DI ERA GLOBALISASI - Nurussakinah Daulay (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Psychology is a discipline that aims to understand human behavior. The difference in human behavior in responding to the presence of stimulus has proven that each human being is unique and not the same, and his needs are also different. No human is the same psychologically even though his physical condition looks the same in plain sight. This which affects the ability of humans is also different when faced with the source of the problem that is being faced. Every human being must constantly develop his competence, so as not to experience a mental crisis that can ultimately lead to pathological disorders. Understanding human uniqueness, especially in cognitive, affective, and psychomotor abilities, will help in the smoothness of the counseling process.Keywords: Psychology; Guidance and counseling.